1999
DOI: 10.1006/viro.1999.9752
|View full text |Cite
|
Sign up to set email alerts
|

Goat Milk Epithelial Cells Are Highly Permissive to CAEV Infection in Vitro

Abstract: The main route of small ruminant lentivirus dissemination is the ingestion of infected cells present in colostrum and milk from infected animals. However, whether only macrophages or other cell subtypes are involved in this transmission is unknown. We derived epithelial cell cultures, 100% cytokeratin positive, from milk of naturally infected and noninfected goats. One such culture, derived from a naturally infected goat, constitutively produced a high titer of virus in the absence of any cytopathic effect. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 20 publications
2
12
0
5
Order By: Relevance
“…MVV can replicate in vitro in a wide variety of ovine cells [30], because the restriction that the virus presents under natural conditions is no longer maintained in vitro [29]. Similarly, CAEV, the caprine counterpart of MVV, can replicate in a variety of cells in vitro [14,15,20,27,28,37] and, significantly, HIV-1 can also productively infect different cell lines in vitro including human OMEC [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MVV can replicate in vitro in a wide variety of ovine cells [30], because the restriction that the virus presents under natural conditions is no longer maintained in vitro [29]. Similarly, CAEV, the caprine counterpart of MVV, can replicate in a variety of cells in vitro [14,15,20,27,28,37] and, significantly, HIV-1 can also productively infect different cell lines in vitro including human OMEC [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been assumed that tissue macrophages are the only target cells for MVV, but several studies have demonstrated that MVV can infect a broader cell range such as oligodendrocytes, astrocytes, fibroblasts [10], endothelial cells [6] and smooth muscle cells [21], among others. It is known that the epithelial cells from granulosa, goat oviduct and those present in goat milk are highly permissive in vitro to the caprine arthritis and encephalitis virus (CAEV) [14,15,27,28]. Even early embryonic cells from in vivo-produced goat embryos transmit this virus [16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast however, our results differ from those reported for HIV-1 replication in epithelial cells in at least two major points. First, all our TIGMEC lines and all primary cultures of GMEC we tested [24] are easily infected by CAEV, whereas four of eleven human primary epithelial cells and one of three cell lines were found resistant to HIV-1 infection [31]. These results may be explained by an inefficient usage of galactosyl-ceramide rather than the CD4 receptor by HIV-1 to enter these cells [15].…”
Section: Discussionmentioning
confidence: 95%
“…CAEV mastitis presents a hardening of the udder during lactation period with diminution of milk production, and involves an important interstitial infiltration and accumulation of lymphocytes. Lymphocytes are not susceptible to infection by CAEV, which has been shown to target cells of the monocytemacrophage lineage, but we have recently shown that primary mammary epithelial cells readily support CAEV infection and may be involved in the pathogenesis of mastitis [24].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation